Solutions for Thriving Ecosystems: 2017-2018 Research Highlights. - CGIAR Research Program on Water, Land and Ecosystems (CGIAR Research Program on Water, Land and Ecosystems, 2018)
When you picture a “thriving ecosystem,” what comes to mind? Your inner eye may turn to images of free-flowing rivers snaking through lush deltas and farm plots heavy with prospering crops. Sadly, the degradation of ecosystems and natural resources is proceeding like never before. Pressure on land and water, pollution from pesticide overuse, and changing weather patterns are among the many factors that impact the livelihoods and food security of millions. The poorest and most marginalized bear the brunt of these burdens. But it doesn’t have to be this way. At the CGIAR Research Program on Water, Land and Ecosystems (WLE), we connect global scientists to find ways for sustainable agriculture to add value to the environment, while also delivering sufficient food, nutrition and income. Many new opportunities for producing safe and nutritious food in thriving ecosystems are emerging. We are developing a portfolio of solutions across ecosystems, sectors and scales—and I invite you to explore some of them on this poster. What they share is the recognition that our ecosystems are intrinsically interlinked. Water use upstream affects food production downstream, while pesticide use on one crop decreases pollination of another. We know that these links exist, and finding ways to address trade-offs and synergies is increasingly urgent for developing the right solutions for sustainable agriculture. A thriving ecosystem is also highly reliant on the policies and institutions that govern it. We must ensure equitable access to knowledge and resources for women, men and marginalized communities. We also need to build capacity to navigate complex uncertainties. Now is time for transformational change. At WLE, we bring together researchers, farmers, implementers and policy makers to ensure innovative technical and policy solutions are developed and implemented. We believe in solutions that provide these partners with the right incentives for change. Only then can the most promising solutions be scaled for the widespread benefit of ecosystems and the people who rely on them. To succeed, the world must move forward on agriculture solutions that don’t just solve one problem, but that are able to consider ecosystems as a whole. Connected, we will Thrive! Izabella Koziell Program Director CGIAR Research Program on Water, Land and Ecosytems